Biochemical markers and assessment of cardiotoxicity during preparative regimen and hematopoietic cell transplantation in acute leukemia - Horacek, J.M.; Pudil, R.; Tichy, M.; Jebavy, L.; Zak, P.; Slovacek, L.; Maly, J. (Experimental Oncology, 2007)
Introduction: Cardiotoxicity is a relatively frequent and potentially serious complication of antitumor treatment. Anthracyclines and other high-dose chemotherapy represent the greatest risk. The aim of the study was to assess cardiotoxicity during preparative regimen (PR) and hematopoietic cell transplantation (HCT) in acute leukemia (AL) with biochemical markers — “N-terminal pro brain natriuretic peptide” (NT-proBNP), cardiac troponin T (cTnT) and creatine kinase MB (CK-MB mass). Methods: Nineteen adult AL patients previously treated with anthracyclines — idarubicine, daunorubicine, mitoxantrone with standard doses for a cycle as 3 х 12 mg/m2, 3 х 50 mg/m2, 3 х 10 mg/m2 accordingly were studied. PR consisted of high-dose cyclophosphamide (HD-C) in combination with busulphan or total body irradiation (TBI). Plasma NT-proBNP, cTnT and CK-MB mass concentrations were measured the day before PR, the day after PR, the day after HCT and 14 days after HCT. Results: Before PR, mean plasma NT-proBNP value was 106.3 ± 55.7 ng/l. After PR, it increased to 426.1 ± 391.5 ng/l. After HCT, a further increase to 847.6 ± 780.6 ng/l was observed. Fourteen days after HCT, the mean NT-proBNP was 330.8±236.8 ng/l. The differences were statistically significant in comparison with the baseline values (p < 0.01). The NT-proBNP elevations were more pronounced in patients with cumulative doses (CD) of anthracyclines above 450 mg/m2 (p < 0.05), in patients with PR containing HD-C and TBI (p < 0.05). In all patients, plasma cTnT and CK-MB mass concentrations remained unchangable during PR and HCT. Conclusion: Our results suggest that administration of PR and HCT is in most AL patients associated with acute neurohumoral activation (significant rise in NT-proBNP). Persistent NT-proBNP elevations, in our study in 12 (63.2 %) patients, indicate subclinical cardiotoxicity (risk for development of heart failure) and require further follow-up. More pronounced NT-proBNP elevations in patients with higher CD of anthracyclines and in patients with PR containing combination of HD-C and TBI confirm that these therapeutic procedures seem to be more cardiotoxic and not very appropriate for patients with cumulation of risk factors for cardiotoxicity. Negative plasma cTnT and CK-MB mass concentrations show no detectable damage of cardiomyocyte structure during PR and HCT. Введение: кардиотоксические осложнения — это относительно частые и потенциально опасные последствия противоопухолевой
терапии. Наибольшую кардиотоксичность отмечают при применении высоких доз химиопрепаратов, в частности антибиотиков
антрациклинового ряда. Целью данного исследования была оценка кардиотоксичности при лекарственной подготовке пациентов
с острым лейкозом (ОЛ) и проведении им трансплантации гематопоэтических стволовых клеток (ГСК), а также определение
следующих биохимических маркеров – N-терминального промозгового натрийуретического пептида (NT-proBNP), сердечного
тропонина T (cTnT) и креатинкиназы MB (CK-MB). Методы: обследованы 19 взрослых пациентов с ОЛ, прошедших предварительное
лечение (ПЛ) с применением антрациклиновых антибиотиков (АА) – идарубицина, даунорубицина, митотриксантрона в дозах 3
х 12 мг/м2
, 3 х 50 мг/м2
, 3 х 10 мг/м2
соответственно. Кроме применения АА, ПЛ включало высокие дозы циклофосфамида
(ВД-Ц) в сочетании с бусульфаном или радиолучевой терапией (РЛТ). Концентрацию NT-proBNP, cTnT и CK-MB определяли
в плазме крови за день до и через день после проведения ПЛ, а также за день до и через 14 дней после трансплантации ГСК.
Результаты: уровень NT-proBNP перед проведением ПЛ составил 106,3 ± 55,7 нг/л, а после повышался до 426,1 ± 391,5 нг/л.
После трансплантации ГСК отмечали дальнейшее возрастание исследуемого показателя до 847,6 ± 780,6 нг/л. Через 14 дней
после трансплантации ГСК концентрация NT-proBNP достигла 330,8 ± 236,8 нг/л, при этом разница была статистически
достоверна по сравнению с исходными значениями (p < 0,01). Повышение уровня NT-proBNP в плазме крови более выражено
у пациентов, получавших АА в суммарной дозе (СД) выше 450 мг/м2
(p < 0,05), а также у больных, получавших ВД-Ц и РЛТ (p
< 0,05). Концентрация cTnT и CK-MB при проведении ПЛ и трансплантации ГСК не изменялась по отношению к исходному
уровню. Выводы: показано, что применение ПЛ и трансплантация ГСК у большинства пациентов с ОЛ сопровождается острой
нейрогуморальной активацией, что проявлялось в существенном повышении уровня NT-proBNP. Постоянно высокий уровень NTproBNP,
отмеченный у 12 (63,2%) пациентов, свидетельствует о бессимптомной кардиотоксичности (риске развития сердечной
недостаточности) и требует последующего врачебного наблюдения больных. Более выраженное повышение уровня NT-proBNP
у пациентов с более высокой СД АА и у больных, получавших ВД-Ц и РЛТ, свидетельствует о том, что такое лечение является
более кардиотоксичным и не рекомендовано для применения в случае наличия факторов риска проявления кардиотоксичности.